The Availability of Open Spaces in Surakarta (A Survey of the Utilization of Open Spaces in Surakarta as a Sport Facility) - Bajuri, Ferry Achmad; Hidayatullah, M Furqon; Kristiyanto, Agus (Journal of Education, Health and Sport, 2019)
The main purposes of the research are: 1) identify open space as a sport facility in Surakarta, 2) tell about some types of sports that utilize open space intensively, 3) tell about community groups that utilize open space to do exercise.This research was conducted at open spaces in Surakarta. The method of the research was descriptive qualitative. The data collection techniques used in this research were interview and observation. The object of the research was the people who utilized open spaces in Surakarta. There were 30 people as the samples of the research that were taken randomly using Proportional Purposive Random Sampling. The data sources in this research were obtained from the people who utilized open spaces as a sport facility. The data analysis techniques used in this research were data collection, data reduction, data presentation, verification and conclusion.The results of the research show that: 1) first, based on the SDI ratio analysis or the comparison of the open spaces in Surakarta to the population of 7 years and above, the availability of open spaces in Surakarta that is only 366,144.44 m² does not meet the ideal level. Second, the open spaces that are most visited and utilized by the people as a sport facility are Gelora Manahan and Car Free Day (CFD) on Slamet Riyadi street. 2) Gelora Manahan and Car Free Day are dominated by both individual sports and group sports from low to high intensity of sports. 3) There are three categories of groups of people who utilize the open spaces. The groups are categorized based on gender, age, and background of activities.